2008
DOI: 10.1111/j.1349-7006.2008.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2D6*10 on recurrence‐free survival in breast cancer patients receiving adjuvant tamoxifen therapy

Abstract: The clinical outcomes of breast cancer patients treated with tamoxifen may be influenced by the activity of cytochrome P450 2D6 (CYP2D6) enzyme because tamixifen is metabolized by CYP2D6 to its active forms of antiestrogenic metabolite, 4-hydroxytamoxifen and endoxifen. We investigated the predictive value of the CYP2D6*10 allele, which decreased CYP2D6 activity, for clinical outcomes of patients that received adjuvant tamoxifen monotherapy after surgical operation on breast cancer. Among 67 patients examined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
1
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(142 citation statements)
references
References 26 publications
(27 reference statements)
5
134
1
2
Order By: Relevance
“…The secondary objective was to determine the association between genotype of the tamoxifen PK-related genes and plasma concentrations of tamoxifen and its metabolites (genotype-PK study) in patients with breast cancer receiving tamoxifen therapy. In the genotype-efficacy study, 282 patients with primary breast cancer (including 67 patients who have been reported previously 7 ) were recruited from September 2007 to April 2009 at Shikoku-*10 collaborative group (Tokushima Breast Care Clinic, Yamakawa Breast Clinic, Shikoku Cancer Center, Kochi University Hospital, and Itoh Surgery and Breast Clinic), Kansai Rosai Hospital, Sapporo Breast Surgical Clinic, and Sapporo Medical University Hospital. All patients were Japanese women pathologically diagnosed with ERand/or PR-positive, invasive breast cancer without distant spread who received adjuvant tamoxifen monotherapy without any other treatments after surgical treatment between 1986 and 2007.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary objective was to determine the association between genotype of the tamoxifen PK-related genes and plasma concentrations of tamoxifen and its metabolites (genotype-PK study) in patients with breast cancer receiving tamoxifen therapy. In the genotype-efficacy study, 282 patients with primary breast cancer (including 67 patients who have been reported previously 7 ) were recruited from September 2007 to April 2009 at Shikoku-*10 collaborative group (Tokushima Breast Care Clinic, Yamakawa Breast Clinic, Shikoku Cancer Center, Kochi University Hospital, and Itoh Surgery and Breast Clinic), Kansai Rosai Hospital, Sapporo Breast Surgical Clinic, and Sapporo Medical University Hospital. All patients were Japanese women pathologically diagnosed with ERand/or PR-positive, invasive breast cancer without distant spread who received adjuvant tamoxifen monotherapy without any other treatments after surgical treatment between 1986 and 2007.…”
Section: Patientsmentioning
confidence: 99%
“…6 Several groups including ours have clarified that loss or decrease of CYP2D6 function by genetic polymorphisms is associated with poorer clinical outcome of tamoxifen treatment in different populations. [7][8][9][10] Although genetic polymorphisms in CYP2D6 are one of the most important determinants for clinical efficacy of tamoxifen, individual differences in responsiveness to tamoxifen still remain, even if the effects of CYP2D6 polymorphisms are considered, suggesting the existence of another genetic factor(s) contributing to individual differences in the formation and elimination of the active metabolites of tamoxifen. However, no large-scale clinical trial exists that investigates the relationship of polymorphisms in tamoxifen pharmacokinetics (PK) -related genes, including CYP2D6, to clinical efficacy of adjuvant tamoxifen therapy.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Higher incidences of recurrence after surgical treatment in breast cancer patients with null-or low-activity genotypes were shown in Caucasian and Japanese populations. 135,136 As patients need to take this drug over a long duration, the genetic diagnosis for tamoxifen treatment may contribute to the improvement of patients' outcomes and the reduction of unnecessary medical cost. Pharmacogenetics information should be useful for predicting the effectiveness, risk of adverse reactions and appropriate dose of drugs for individual patients' , and may contribute to the establishment of 'personalized medicine' , the concept of 'an appropriate dose of a right drug to a right patient' .…”
Section: Genetic Variations In Pharmacogenetics and Pharmacogenomicsmentioning
confidence: 99%
“…Compared with CYP2D6 extensive metabolizers, poor metabolizers exhibit a 3-fold higher risk of recurrence, 2,3 whereas CYP2D6 intermediate metabolizers (those with ''intermediate'' reductions in endoxifen concentrations) exhibit a lower risk of recurrence. [2][3][4][5] Given the characteristics of the study by Okishiro et al (median follow-up, 56 months among 173 patients, with 25% with the *10/*10 genotype; enrollment period, 6 years; follow-up, 4 years; and 5-year recurrence-free survival rate, 90% in the *10/*10 genotype subgroup), a 2-sided a ¼ .05 logrank test has a power of 26% to detect a 2-fold increase in the hazard of disease recurrence in the *10/*10 carriers relative to *10/wild type (wt) or wt/wt carriers.…”
mentioning
confidence: 99%